2009
DOI: 10.1152/ajpheart.00349.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of arachidonic acid lipoxygenase metabolites in the regulation of vascular tone

Abstract: Stimulation of vascular endothelial cells with agonists such as acetylcholine (ACh) or bradykinin or with shear stress activates phospholipases and releases arachidonic acid (AA). AA is metabolized by cyclooxygenases, cytochrome P-450s, and lipoxygenases (LOs) to vasoactive products. In some arteries, a substantial component of the vasodilator response is dependent on LO metabolites of AA. Nitric oxide (NO)- and prostaglandin (PG)-independent vasodilatory responses to ACh and AA are reduced by inhibitors of LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 160 publications
(270 reference statements)
3
98
0
3
Order By: Relevance
“…Symmetric and asymmetric dimethylarginine (SDMA and ADMA), which are known as a cardiovascular risk factors, compete with L-arginine for transportation into cells, thus reducing the substrate for NO synthesis (Vallance et al, 1992;MacAllister et al, 1996;Lluch et al, 2006). Furthermore, arachidonic and linoleic acids products (e.g., hydroxy-eicosatetranoic acids (HETE), prostaglandins, and leukotrienes) are determinants in the regulation of the vascular tone and possibly contribute to pulmonary hypertension (Ma et al 2011;Chawengsub et al, 2009). In particular, serotonin has been shown to increase pulmonary artery pressure in hypoxia (Morecroft et al, 2007), partially in consequence of ROS-dependent generation of the transporter, providing serotonin to the site of action, has been demonstrated (Lawrie et al, 2005).…”
Section: Oxidative Stress In Hypobaric Hypoxia and Influence On Vessementioning
confidence: 99%
“…Symmetric and asymmetric dimethylarginine (SDMA and ADMA), which are known as a cardiovascular risk factors, compete with L-arginine for transportation into cells, thus reducing the substrate for NO synthesis (Vallance et al, 1992;MacAllister et al, 1996;Lluch et al, 2006). Furthermore, arachidonic and linoleic acids products (e.g., hydroxy-eicosatetranoic acids (HETE), prostaglandins, and leukotrienes) are determinants in the regulation of the vascular tone and possibly contribute to pulmonary hypertension (Ma et al 2011;Chawengsub et al, 2009). In particular, serotonin has been shown to increase pulmonary artery pressure in hypoxia (Morecroft et al, 2007), partially in consequence of ROS-dependent generation of the transporter, providing serotonin to the site of action, has been demonstrated (Lawrie et al, 2005).…”
Section: Oxidative Stress In Hypobaric Hypoxia and Influence On Vessementioning
confidence: 99%
“…Available data suggest that lipoxygenases contribute to in vivo metabolism of endobiotics and xenobiotics in mammals (Kulkarni, 2001). Recent reviews describe the role of lipoxygenase in cancer (Bhattacharya et al, 2009;Pidgeon et al, 2007;Moreno, 2009), inflammation (Duroudier et al, 2009;Hersberger, 2010) and vascular biology (Chawengsub et al, 2009;Mochizuki & Kwon, 2008) and for an extensive presentation of the role of eicosanoids in prevention and management of diseases the reader is referred to the review of Szefel et al (2011).…”
Section: In Humansmentioning
confidence: 99%
“…Calcium ion participates in the many process, including release, activation, and effectiveness of many inflammatory mediators, such as activation of phospholipase A 2 (PLA 2 ), increasing the production of arachidonic acid metabolites (Chawengsub et al, 2009), NO synthesis (Koya and King, 1998), interleukins releasing, mediators of exocytosis, and chemotactic responses (Lam and Ferrell, 1993). On the other hand, evidences showed that the voltage calcium channel blockers (CCBs) cause inhibition of NO production and the enzymes responsible for the synthesis of prostaglandins (Lam and Ferrell, 1992), and decrease the release of histamine, bradykinin, serotonin, arachidonic acid metabolites, and leukotrienes (Fogel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%